BEYOND TRIPTANS: SYSTEMATIC REVIEW FOCUSING ON THE EFFICACY AND SAFETY PROFILE OF CGRP RECEPTOR ANTAGONISTS IN MIGRAINE MANAGEMENT - Mikołaj Szulewski; Gabriela Bajor; Zofia Gniadek; Joanna Kozak; Aleksandra Salagierska; Kacper Melka; Patrycja Machno; Patryk Matuszczak; Agata Pszczółka; Wiktoria Jurczyk-Florkiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Despite the availability of traditional pharmacotherapies, including triptans and nonsteroidal anti-inflammatory drugs (NSAIDs), clinical value is often limited by suboptimal efficacy, significant cardiovascular contraindications, and the risk of medication-overuse headache (MOH). This study aims to evaluate the clinical efficacy and safety of rapidly developing calcitonin gene-related peptide (CGRP) receptor antagonists named ‘gepants’. Material and methods: A systematic review of scientific literature was performed to evaluate the efficacy of novel antimigraine agents. A structured search of the PubMed database was conducted using keywords including "migraine", "gepant", and "CGRP receptor antagonists." Emphasis was placed on clinical trials, RCTs, and meta-analyses, supplemented by references to neurological textbooks to provide clinical context. Results: Analysis of clinical data indicates that daily administered gepants reduce mean monthly migraine days (MMDs) compared to placebo in preventive treatment model. Furthermore, gepants proved their efficacy in acute migraine treatment, providing pain relief and the absence of the most bothersome symptoms (MBS). Multiple studies evaluating novel gepants have reported safety profiles comparable to placebo. In addition, gepants do not exert vasoconstrictive effects, making them a viable candidate for triptan-unsuitable patients or those who had documented adverse events (AEs) of traditional oral preventive medications (OPMs). Conclusions: Novel CGRP receptor antagonists represent a significant advancement in migraine therapy. By providing high tolerability and efficacy without the risk of MOH, hepatotoxicity or cardiovascular events, gepants emerge as a transformative option for both acute relief and prophylaxis in adult triptan-unsuitable patients suffering from migraine.